Surgical Correction of Grown Up Tetralogy of Fallot (Medical Forum Monthly, 2024)
Objective: To get an audit of outcome of our patients operated for total correction for grown up Tetralogy of FallotStudy Design: Observational / analytic study.Place and Duration of Study: This study was conducted at the Department of Cardiac Surgery, NICVD, Karachi from January 2015 to August 2016.Materials and Methods: We reviewed our surgical record and collected the data of patients with age 18 years and beyond, who underwent for total correction in Tetralogy of Fallot. We had included the patients whose prospective record of their surgical as well as socioeconomic outcome.Results: Total 35 patients were identified , out of 35 patients 19 were selected as final cohort of patients for our study they included 11(48%) females and 8 (42%) males with age range of 18 to 28 years. Procedures for TOF repair included trans-annular patch (n=7), trans-ventricular (n=5) , trans-atrial (n=2). While the remaining patients (n=3) had combined approaches ( tran-atrial with trans-pulmoary or trans-ventricular with trans-pulmonary). The 30-day mortality rate was 16% (right ventricular failure n=1; tamponade n=1; low cardiac output with pulmonary edema as a result of residual ventricular septal defect n=1) . 3 patients were re-explored due to mediastinal bleeding with one of them had developed cardiac tamponade.Follow-up of minimum 3 month to maximum of 15 months was feasible in 16 out of 19 survivors, improvement in functional class (NYHA) was observed in 11 patients.Conclusion: Complete repair of TOF in patients 18 years or older is possible but carries increased operative risk. Survivors have improvement in their functional class as well as social status however it is difficult to commit on economical productivity of patients.